Evaluation of the green open space policy of bekasi city in achieving development indicators (sustainable settlements) - Najmuddin Najmuddin; Sucahyanto Muzani Jalaluddin (Faculty of Economics and Business Mulawarman University, 2019)
The objective of this research was to evaluate the green open space policy of Bekasi City in achieving development indicators (sustainable settlements). It was a qualitative research with evaluation method conducted in the City of Bekasi, West Java in 2018. The data were collected through participant observation using interview, observation, and document study. The data was analysed and interpretated through (1) Data reduction, sorting, concentration and simplification of